2019
DOI: 10.1002/slct.201900778
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Assisted Extraction of Triterpenoid Saponins from Pseuderanthemum palatiferum (Nees) Radlk. Dry Leaf Powder and Bioactivities Examination of Extracts

Abstract: Triterpenoid saponins were extracted from of Pseuderanthemum palatiferum (Nees) Radlk. dry leaf powder by using enzyme‐assisted extraction method. Effects of single factors on total saponins content (TSC) were investigated. Then, a full factorial design with two levels was conducted to screen the main factors affecting TSC. Two main factors as extraction temperature and time were determined. Response Surface Methodology with central composite design was used to study simultaneous effects of these factors on TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…In the present study, an extraction temperature of 60EC was selected for all the subsequent experiments (determination of the extraction time). The optimal extraction temperature determined in the present study was slightly higher than that reported by Huy et al (2019) who extracted triterpenoid saponins from the dried root and leaf of Pseuderanthemum palatiferum (Nees) Radlk at 55EC by viscozyme-assisted extraction (viscozyme is a multienzyme complex containing a wide range of carbohydrases, including arabanase, cellulase, β-glucanase, hemicellulase, and xylanase). In addition, the optimal extraction temperature determined in the present study was also significantly higher than that reported by Pan and Wu (2014), who used the CAE method to extract polysaccharides from garlic at 45EC.…”
Section: Effect Of the Extraction Temperature On Tsc Extractioncontrasting
confidence: 52%
“…In the present study, an extraction temperature of 60EC was selected for all the subsequent experiments (determination of the extraction time). The optimal extraction temperature determined in the present study was slightly higher than that reported by Huy et al (2019) who extracted triterpenoid saponins from the dried root and leaf of Pseuderanthemum palatiferum (Nees) Radlk at 55EC by viscozyme-assisted extraction (viscozyme is a multienzyme complex containing a wide range of carbohydrases, including arabanase, cellulase, β-glucanase, hemicellulase, and xylanase). In addition, the optimal extraction temperature determined in the present study was also significantly higher than that reported by Pan and Wu (2014), who used the CAE method to extract polysaccharides from garlic at 45EC.…”
Section: Effect Of the Extraction Temperature On Tsc Extractioncontrasting
confidence: 52%
“…To determine the factors affecting triterpenoid content from G. lucidum by UAEE, five factors were selected including enzyme concentration, ethanol: material ratio, ultrasonic temperature, ultrasonic time, and ultrasonic power. The selected factors have a survey range based on previous studies (Dat et al, 2021; Huy et al, 2019). Experimental design according to PBD for 5 factors and 12 experiments to determine the influence of each factor on triterpenoid content.…”
Section: Methodsmentioning
confidence: 99%
“…For a long time, it has been reported that since multivariable optimisation only focuses on the method of ′one‐factor‐at‐a‐time′, it is impossible to investigate the communication between independent factors to give ambiguous details of the impacts of all determinants. To overcome these shortcomings, response surface methodology (RSM) is introduced as an effective statistical model to estimate the interactions between multiple variables [25–27] . In this study, extraction power, extraction temperature, extraction times and other factors were optimised by RSM.…”
Section: Introductionmentioning
confidence: 99%